Pengaruh Reformasi Administrasi Perpajakan terhadap Kepatuhan Wajib Pajak (Studi pada Wajib Pajak Orang Pribadi di KPP Pratama Semarang Gayamsari) - Aryani, Shafarita Fajar; Budiman, Judi (Innovative: Journal Of Social Science Research, 2025)
Taxation has a pivotal function in facilitating national development as the primary source of government revenue. The tax administration reform implemented by the Directorate General of Taxes (DGT) through the modernization of the administrative system and the alignment of the Population Identification Number (NIK) with the Taxpayer Identification Number (NPWP) is anticipated to enhance compliance among Individual Taxpayers (WP). This study seeks to examine the impact of modernizing the tax administration system and aligning the NIK with the NPWP on taxpayer compliance at the Semarang Gayamsari Pratama Tax Office. A quantitative methodology employing the causal-associative technique was utilized, involving 100 taxpayer respondents selected by purposive sampling. Primary data were gathered by a questionnaire and analyzed via multiple linear regression using SPSS 26.0, following the completion of validity, reliability, and classical assumption assessments. The study's results demonstrate that the two independent variables, specifically the modernization of the tax administration system and the alignment of NIK with NPWP, exert a considerable beneficial influence on the compliance of Individual Taxpayers. This discovery suggests that accessibility to the administrative system and the integration of identity data significantly enhance tax compliance. This research implies the necessity to enhance socialization and improve the system to optimally accomplish the national tax revenue target.